Predictor factors of pulmonary hypertension in children with left-to-right shunting in acyanotic congenital heart disease - Weny Inrianto; Indah Kartika Murni; Ida Safitri (Indonesian Pediatric Society, 2021)
Background Left-to-right shunting in acyanotic congenital heart disease (CHD) is the most common type of defect in childhood heart disease. Limited access to specialist health services causes delays in CHD management. In limited resource settings, identification of factors that influence the occurrence of pulmonary hypertension is important in order to decide which patients should be prioritized for defect closure to prevent further complications. Objective To determine predictive factors of pulmonary hypertension after a left-to-right shunt CHD diagnosis. Methods This retrospective cohort study included children aged 1 month to 17 years with isolated atrial septal defect, or ventricular septal defect, or patent ductus arteriosus. Potential predictors studied were iron deficiency anemia, mitral regurgitation, pneumonia, and heart failure. Bivariate analysis was done with Chi-square test and multivariate analysis was done with Cox regression to determine the hazard ratio. Results Pulmonary hypertension occurred in 68 of 176 subjects. Iron deficiency anemia, mitral regurgitation, and pneumonia were not predictives of pulmonary hypertension. However, heart failure was a significant predictive factor for pulmonary hypertension, with a hazard ratio of 4.1 (95%CI 2.2 to 7.5; P=0.001). Conclusions Heart failure is a predictive factor of pulmonary hypertension in children with left-to-right shunting in acyanotic CHD.